Mobile Assisted Personalised Language Learning (MAPLL) : Sustaining Rural School Learners’ Distance Learning - SONG , Sheng Jia; TAN, Kim Hua; Alias, Jamsari; Yaacob, Mashitoh (Journal of Ecohumanism, 2024)
This study aims to investigate the application of an adapted model, namely Mobile Assisted Personalised Language Learning (MAPLL) via e-modules, in tackling the hardship of rural schools learners’ online language learning during the emergent outbreak of coronavirus (COVID-19), with the vision of ensuring digital equity among learners.The underlying research main concepts and theories are portrayed. Technology-mediated learning theory, cognitivism, constructivism and connectivism stand out, allowing a consolidate foundation for the understanding of context investigation. To evaluate the effectiveness of chosen model, this study sets forth findings from a mixed method case study among rural secondary school learners in Malaysia. In this study, learners undergo English vocabulary lessons through MAPLL model. Data collection was carried out through questionnaires and semi-structured interview. The study results strengthen foundation of MAPLL model in reducing digital gap. Learners experienced positive impacts in terms of technology, flexibility, learning approach, learning content, and mood. The practical and theoretical implications of this research are discussed, providing insights into how MAPLL model can be applied or influence practices in the field of education.